Using correction parameters to improve real-time video interpolation in low-cost VLSI implementation. (November 2021) - Guan, Haowei; Zhang, Zhang; Cheng, Xin; Yang, Yizhong; Xie, Guangjun
Abstract: This paper introduces a relative-contrast-based algorithm to improve VLSI real-time video interpolation image quality. A relative-contrast-based adaptive interpolation correction factor w i is formed to correct linear interpolation algorithm. A LUT is integrated in proposed design to simplify the logarithmic process which is the key procedure in w i generation. Proposed algorithm improved the image quality and decline resource requirements compared with similar efforts. In comprehensive, the VLSI implementation performance shows predictably image quality improvements with sensible area cost. The chip test result shows interpolation function can support up to 1920x1080 at 60FPS, both scaler up and down.